Practice of advertising theories by Standard Chartered Bank (SCB) SBU: visa signature credit card - Hasan, Tawfiq (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.